2018
DOI: 10.1101/423905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple C2 domains and Transmembrane region Proteins (MCTPs) tether membranes at plasmodesmata

Abstract: In eukaryotes, membrane contact sites (MCS) allow direct communication between organelles. Plants have evolved unique MCS, the plasmodesmata intercellular pores, which combine endoplasmic reticulum (ER) - plasma membrane (PM) contacts with regulation of cell-to-cell signalling. The molecular mechanism and function of membrane tethering within plasmodesmata remains unknown.Here we show that the Multiple C2 domains and Transmembrane region Protein (MCTP) family, key regulators of cell-to-cell signalling in plant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 100 publications
0
58
0
Order By: Relevance
“…PD are viewed as signalling hub (Lee, 2015) and special membrane contact sites (MCSs) (Tilsner & Torrance, 2011;P erez-Sancho et al, 2016;Tilsner et al, 2016;Bayer et al, 2017;Brault et al, 2019), with lipid rafts or nanodomains (NDs) enriched in sterol and sphingolipids resident on the PD-PM (Raffaele et al, 2009;Mongrand et al, 2010;Tilsner & Torrance, 2011;Grison et al, 2015;Yan et al, 2019). Several functional proteins and signalling lipids are recruited to these NDs by lateral segregation to regulate PD permeability.…”
Section: Discussionmentioning
confidence: 99%
“…PD are viewed as signalling hub (Lee, 2015) and special membrane contact sites (MCSs) (Tilsner & Torrance, 2011;P erez-Sancho et al, 2016;Tilsner et al, 2016;Bayer et al, 2017;Brault et al, 2019), with lipid rafts or nanodomains (NDs) enriched in sterol and sphingolipids resident on the PD-PM (Raffaele et al, 2009;Mongrand et al, 2010;Tilsner & Torrance, 2011;Grison et al, 2015;Yan et al, 2019). Several functional proteins and signalling lipids are recruited to these NDs by lateral segregation to regulate PD permeability.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the recently published Arabidopsis plasmodesmata-proteome (Brault et al, 2019) identified several members of the RLK family present in the plasmodesmata fraction with clade III members being predominant (Supplemental Table S1). As plasmodesmata have been reported to be composed of sterol-and sphingolipid-enriched microdomains (Grison et al, 2015a; Nicolas et al, 2017), we focused on RLKs, which may preferentially associate with lipid microdomains by cross referencing the accessions with seven published detergent-resistant membrane (DRM) proteomes (Shahollari et al, 2004(Shahollari et al, , 2005Kierszniowska et al, 2009;Minami et al, 2009;Keinath et al, 2010;Demir et al, 2013;Srivastava et al, 2013;Szymanski et al, 2015).…”
Section: The Pm-associated Lrr-rlks Qsk1 and Imk2 Dynamically Associamentioning
confidence: 99%
“…We used the label-free plasmodesmata proteomic analysis of Brault et al (2019) to select RLK candidates. For that, all members of the LRR-RLK family that displayed with a significant fold change (plasmodesmata/PM enrichment ratio .…”
Section: Proteomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant feature of the PD is a strand of endoplasmic reticulum (ER) that traverses the pore and is tethered tightly to the plasma membrane (PM) by unidentified spokes [5]. Recent study has demonstrated that multiple C2 domains and transmembrane region proteins (MCTPs) are core PD proteins involved in tethering ER and PM [6].…”
Section: Introductionmentioning
confidence: 99%